When truth gives out - Richard, Mark. (Oxford : Oxford University Press, 2008)
In this accessible book, Mark Richard argues that the performative and expressive can trump the semantic, making truth the wrong dimension for evaluating a sentence. He explains what it is for truth to be relative, rebuts objections to relativism assesses objections to expressivism, and gives a novel account of matters of taste.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Truth; Relativity